Political Aspect as the Main Constraint to Realize Green Growth In East Kalimantan - Hartanto, Hartanto (Journal of International Relations on Energy Affairs, 2020)
The journey of economic growth and development is on an unsustainable trajectory, marked by conditions that endanger natural assets and environmental services, both of which form the basis of long-term economic growth and human well-being. Indonesia is the 6th largest emitter in the world, while East Kalimantan itself is the 6th largest emitter nationally. The fundamental question that often arises in the author's mind is "can economic prosperity be obtained by marginalizing natural factors which are then deemed insignificant? In response to this, a concept known as green growth emerged. To discuss this, the author uses qualitative methods. This method provides a form of data collection and analysis that focuses on emphasizing and understanding meaning. The data collected comes from official documents and other supporting documents. The author makes interpretations of what is seen, heard and understood. The results showed that in order to achieve Green economic growth in East Kalimantan, political, economic and social aspects must be considered.Political aspects are the most important thing because policies play a key role in realizing green growth, policy makers can build green growth strategies, with the help of their commitments. However, the political, social and economic aspects are interrelated and mutually supportive.